2020
DOI: 10.17220/ijpes.2020.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The Predictor Role of the Search for Meaning in Life in the Determination of High School Students’ Lifelong Learning Tendencies

Abstract: The current study aims to determine the extent to which high school students' lifelong learning tendencies are predicted by their search for meaning in life. The study was conducted on a total of 352 senior high school students (165 females, 187 males) attending high schools located in the Bodrum District of the city of Muğla. The data of the study was collected by using a personal information form developed by the researchers, The Lifelong Learning Tendencies Scale developed by Diker-Coşkun (2009) and the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Considering studies examining the relationship between variables, Asiloğulları (2020) found moderate positive relationships between lifelong learning tendencies, the meaning of life, and goals. Kılınç and Uzun (2020) determined that there was a moderate positive relationship between lifelong learning tendency and the meaning of life. However, Argon et al (2016) concluded that there was a weak positive relationship between lifelong learning tendency and career adaptability.…”
Section: Discussion Regarding the Second Research Questionmentioning
confidence: 99%
“…Considering studies examining the relationship between variables, Asiloğulları (2020) found moderate positive relationships between lifelong learning tendencies, the meaning of life, and goals. Kılınç and Uzun (2020) determined that there was a moderate positive relationship between lifelong learning tendency and the meaning of life. However, Argon et al (2016) concluded that there was a weak positive relationship between lifelong learning tendency and career adaptability.…”
Section: Discussion Regarding the Second Research Questionmentioning
confidence: 99%